(untitled) (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2025)
Investigation of adsorption of Congo Red (CR) and Methylene Blue (MB) dyes by coffee skin carbon chitosan composite beads (CCCB) has been carried out. The adsorbent was synthesized with varying mass ratio of chitosan and carbon. The composite was synthesized with PVA as a crosslinker agent. This research was carried out in several stages for adsorbent preparation, the effect of contact time (adsorption kinetics), and isotherm adsorption. Adsorption studies were carried out using a batch system. The effect of adsorption contact time was carried out at a contact time of 15 - 150 minutes, adsorbent dose of 10 g/L with dyes volume of 10 mL and initial dyes concentration of 25 mg/L. The optimum adsorption time of MB was obtained at 90 minutes with the adsorption percentage of 91.50% with 1:1 carbon chitosan composite beads. The optimum adsorption time of CR was obtained at 150 minutes with the adsorption percentage of 96.01% with chitosan beads. The kinetics result is in line with pseudo second order rate equation for all application. The isotherm studies almost follow the Langmuir isotherm models.